Single-Cell RNA Sequencing Reveals B Cells Are Important Regulators in Fracture Healing - Zhang, Hao; Wang, Renkai; Wang, Guangchao; Zhang, Bo; Wang, Chao; Li, Di; Ding, Chen; Wei, Qiang; Fan, Zhenyu; Tang, Hao; Ji, Fang (Frontiers in Endocrinology, 2021)
Bone marrow microenvironment is mainly composed of immune cells and stromal cells that play an important role in fracture healing. Although immune cells have been identified in mouse bone marrow, variations in the numbers and type of immune cells in fracture healing process are still not well defined. Here, single-cell RNA-Sequencing (scRNA-seq) was used to identify immune cells in fracture tissues, including neutrophils, monocytes, T cells, B cells and plasma cells etc. We found that B cells decreased significantly in the early stage of fracture healing. Furthermore, B cells were identified in mice fracture models and we found that B cells decreased significantly during the epiphyseal phase and gradually returned to normal during the epiphyseal transformation phase of fracture healing, which was the opposite to bone formation and resorption activities. Meaningfully, B-cell derived exosomes inhibited bone homeostasis in fracture healing. Mechanistically, human beings promote fracture healing by decreasing the number of B cells during the epiphyseal phase. With the number of osteoblasts increasing, human body gradually recovers the number of B cells during callus reconstruction stage, which reduces additional bone regeneration. Thus, our findings indicate that B cell is a key regulator of fracture healing and inhibits excessive bone regeneration by producing multiple osteoblasts inhibitors.